Retinal microvascular abnormalities in major depression - Sadykov, Evgenii; Hosák, Ladislav; Stěpanov, Alexandr; Zapletalová, Jana; Studnička, Jan (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2024)
BACKGROUND: The aim of our study was to find a possible association between retinal microvascular abnormality and major depression in a non-geriatric population. METHOD: The participants with major depression were hospitalised at the University Hospital in Hradec Kralove, Department of Psychiatry. Retinal images were obtained using a stationary Fundus camera FF450 by Zeiss and a hand-held camera by oDocs. RESULTS: Fifty patients (men n=18, women n=32) aged 16 to 55 (men's average age 33.7±9.9 years, women's average age 37.9±11.5 years) were compared with fifty mentally healthy subjects (men n=28, women n=22) aged 18 to 61 (men's average age 35.3±9.2 years, women's average age 36.6±10.6 years) in a cross-sectional design. The patients were diagnosed with a single depressive episode (n=26) or a recurrent depressive disorder (n=24) according to the ICD-10 classification. Our results confirmed significant microvascular changes in the retina in patients with depressive disorder in comparison to the control group of mentally healthy subjects, with significantly larger arteriolar (P<0.0001) as well as venular (P<0.001-0.0001) calibres in major depression. CONCLUSION: According to the literature, acute and chronic neuroinflammation is associated with changes in microvascular form and function. The endothelium becomes a major participant in the inflammatory response damaging the surrounding tissue and its function. Because the retina and brain tissue share a common embryonic origin, we suspect similar microvascular pathology in the retina and in the brain in major depression. Our results may contribute to a better understanding of depression etiopathogenesis and to its personalized treatment.
Keywords: nemoci retiny; Humans; Case-Control Studies; lidé středního věku; studie případů a kontrol; retinální cévy; Depressive Disorder, Major; Retinal Diseases; Female; mladý dospělý; dospělí; lidé; Microvessels; Adult; depresivní porucha unipolární; ženské pohlaví; Male; Middle Aged; Adolescent; mikrocévy; Cross-Sectional Studies; Young Adult; mužské pohlaví; Retinal Vessels; průřezové studie; mladiství